Essential techniques of alveolar bone augmentation in implant dentistry a surgical manual - Tolstunov, Len (Wiley, 2022)
"The second edition of Essential Techniques of Alveolar Bone Augmentation in Implant Dentistry: A Surgical Manual presents a variety of key techniques for ensuring proper bone width and height for dental implant placement. Enabling clinicians and dental students to rapidly locate information for cases requiring bone augmentation, this highly practical reference covers ridge preservation, horizontal and vertical ridge augmentation, soft tissue grafting for implant site development, tissue engineering techniques, and surgical alternatives to bone grafting in implant dentistry. Succinct chapters written by a panel of leading practitioners include step-by-step descriptions of each procedure--supported by information on diagnosis and treatment planning and more than 1,000 high-quality clinical images and illustrations. This fully up to date second edition includes new coverage of 3D alveolar ridge defect reconstruction, procedures for vertical bone augmentation in the posterior maxilla, complete arch dental implant treatment using photogrammetry, metal-ceramic transitional maxillary implant rehabilitation, ridge-split expansion using piezoelectric surgery, and more. Essential Techniques of Alveolar Bone Augmentation in Implant Dentistry: A Surgical Manual, Second Edition is a must-have for both novice and experienced dental clinicians, implant dentists, oral surgeons, prosthodontists, and periodontists, and an invaluable resource for dental students and trainees"--